Effect of Optisol Supplementation With 0.255 μg/mL Amphotericin B on Elimination of Yeast at 5°C. Issue 7 (July 2019) - Tran, Devin; Dhaliwal, Deepinder; Kamyar, Roheena; Jhanji, Vishal; Kowalski, Regis P.
Abstract : Purpose: Fungal infections in lamellar keratoplasty are a growing concern. Optisol-GS does not contain an antifungal agent and supplementation with 0.255 μg/mL Amphotericin B (AmpB) has been considered. This study tested the ability of 0.255 μg/mL AmpB in Optisol-GS to eliminate yeast contamination of corneal tissue. Methods: Three isolates of Candida albicans, 1 of Candida parapsilosis, and 1 of Candida glabrata were tested in Optisol with and without AmpB. Corneoscleral rims stored at −80°C were thawed and placed in 10 multiwell plates (4 per plate). The rims were inoculated with 4 respective loads of yeast: 0, 10 1, 10 2, and 10 3 colony-forming units in 2 sets of 5 for 5 yeasts. One set was filled with Optisol plus AmpB and the other with Optisol only. All 10 plates were incubated at cold storage (2°C–8°C) for 48 hours. After 48 hours, all corneal rims were placed into 10 mL of yeast extract peptone dextrose medium; a swab culture of each well was plated onto Sabouraud plates; and all plates with the remaining Optisol were incubated at 30°C. Yeast growth was monitored for 10 days. Minimum inhibitory concentration and minimum fungicidal concentration were determined. Results: All corneoscleral specimens were positive regardless of fungal load or presence of AmpB. All controls remained negative. Minimum inhibitory concentrations and minimum fungicidal concentrations were equivalent and ranged between 0.5 and 2.0 μg/mL. Conclusions: AmpB at a concentration of 0.255 μg/mL in Optisol-GS at cold storage (2°C–8°C) over 48 hours did not eliminate yeast from corneal tissue.